Ar-Ar Geochronology and Sr-Nd-Pb-O Isotopic Systematics of the Post-collisional Volcanic Rocks from the Karapınar-Karacadağ Area (Central Anatolia, Turkey): An Alternative Model for Orogenic Geochemical Signature in Sodic Alkali Basalts - Gencoğlu Korkmaz,G.; Kurt,H.; Asan,K.; Leybourne,M. (Journal of Geosciences, 2022)
The Plio-Quaternary post-collisional volcanism in the Karapınar area is represented by two occurrences: (1) Karacadağ Volcanic Complex (KCVC) and (2) Karapınar Volcanic Field (KPVF). The investigated volcanic units are the southwestern part of the Neogene to Quaternary Cappadocia Volcanic Province (CVP) in Central Anatolia. The CVP generally displays calc-alkaline affinity in the Late Miocene to Pliocene rocks, but both calc-alkaline and sodic alkaline affinity in the Plio-Quaternary rocks, all of which have an orogenic geochemical signature. Such a volcanic activity contradicts the Western and Eastern Anatolian volcanism characterized by anorogenic OIB-like sodic alkaline volcanic rocks postdating early orogenic calc-alkaline ones. We hypothesize that such temporal and geochemical variations in the investigated rocks result from crustal contamination and present major and trace element chemistry and Sr-Nd-Pb-O isotope geochemistry, coupled with 40Ar/39Ar geochronology data to restrict the genesis and evolution of the rocks. The Neogene Karacadağ volcanic rocks are represented by lava flows, domes and their pyroclastic equivalents constituting a stratovolcano, and dated by new 40Ar/39Ar ages of 5.65 to 5.43 Ma. They are mainly composed of andesitic, rarely basaltic, dacitic and trachytic rocks and have a calc-alkaline character. Constituting a monogenetic volcanic field, the Quaternary Karapınar volcanic rocks are typically formed by cinder cones, maars and associated lavas, including xenoliths and xenocrysts plucked from the Karacadağ rocks. They comprise basaltic to andesitic rocks with a transitional affinity, from sodic alkaline to calc-alkaline. Both the Karacadağ and Karapınar volcanic rocks display incompatible trace element patterns rather characteristic for orogenic volcanic rocks. The Sr, Nd and Pb isotopic systematics of both units show a relatively narrow range, but their δ18O values are markedly different. The Karacadag volcanic rocks have δ18O values ranging from 7.5 to 8.9 ‰, resembling those of subduction-related basalts, but the Karapınar volcanics have δ18O ratios between 5.7 and 6.5 ‰ corresponding to OIB-like rocks. Additionally, δ18O values and 87Sr/86Sr ratios correlate positively with SiO2 in the rocks, indicating that contamination played an important role during differentiation processes. All the data obtained suggest that the Karacadağ basaltic rocks stemmed from a subduction-modified lithospheric mantle source. On the other hand, the origin of the Karapınar basaltic rocks can be explained in terms of OIB-like melts contaminated with the Karacadağ volcanic rocks to gain orogenic geochemical signature, which may be an alternative model for the origin of the CVP sodic alkali basalts.
Keywords: contamination; geochronology; isotope geochemistry; post-collisional; OIB